Effects of different alkali mixtures on physicochemical, microstructural, and powder properties of alkalized cocoa - Akman, Perihan Kuebra; Ermis, Ertan; Daskaya-Dikmen, Ceren; Toker, Omer Said (SPRINGER, 2024)
Alkalization changes the physicochemical, bioactive, and powder flow properties of cocoa powders, so it is an essential factor affecting the quality of cocoa products. This study investigated the relationship of the alkalization process with physicochemical properties such as color, pH, and bioactive properties such as total phenolic, flavonoid, and antioxidant capacity of cocoa powders. For this purpose, natural cocoa powders were alkalized using sodium hydroxide (NaOH) or potassium carbonate (K2CO3), or potassium hydroxide (KOH) solutions at their different concentrations. The browning index, darkness, and pH values increased while the total phenolic content, flavonoid, and antioxidant capacity decreased depending on the type of alkali used. FTIR spectra revealed changes in the stretching vibrations in the molecular structure of alkalized cocoa powders. Even though the alkalization process did not affect the microstructure of cocoa particles visibly, treatment with different alkali agents altered the thermal behavior, compressibility and caused a decrease in the powder flowability.
Keywords: Cocoa; Alkalization; Powder flowability; Bulk density; ANTIOXIDANT ACTIVITY; PHENOLIC-COMPOUNDS; PRODUCTS; FLAVANOL; IMPACT; COLOR; WHEAT; Food Science & Technology